1972
DOI: 10.5636/jgg.24.459
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of NRM of Deccan Traps Basalts in India

Abstract: Samples of Deccan Trap basalts from all flows in the Mahabaleshwar and Amboli cliff sections in western India have been analysed by the thermomagnetic, and X-ray techniques.The principal conclusions are: 1) the NRM was stablized by oxidation of titanomagnetite shortly after eruption of lavas; 2) low-temperature oxidation of titanomagnetite can occur at ordinary temperatures is within a million years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1974
1974
1985
1985

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(16 reference statements)
1
1
0
Order By: Relevance
“…These curves bear a strong resemblance to J,-T curves obtained in air on Deccan traps basalts in India (Kinoshita & Aoki 1972), which are of similar age as the Disko basalts. These authors found two contrasting types (' I, I1 ') of magnetic behaviour, resembling our classes n and r, except that their study included samples from flows having stable N polarity as well as from stable4 flows, with each type of behaviour occurring among samples from both stable polarity groups.…”
Section: Therrnornagnetic Measurementssupporting
confidence: 63%
“…These curves bear a strong resemblance to J,-T curves obtained in air on Deccan traps basalts in India (Kinoshita & Aoki 1972), which are of similar age as the Disko basalts. These authors found two contrasting types (' I, I1 ') of magnetic behaviour, resembling our classes n and r, except that their study included samples from flows having stable N polarity as well as from stable4 flows, with each type of behaviour occurring among samples from both stable polarity groups.…”
Section: Therrnornagnetic Measurementssupporting
confidence: 63%
“…The Curie temperatures of these samples range from 440° to 585°C, but most of the Curie temperatures are distributed between 560° and 580°C, showing a predominance of ferromagnetic minerals of nearly pure magnetite composition. The thermomagnetic behavior of the samples shows the most ferromagnetic minerals are more or less oxidized through unmixing process of Ti-rich titanomagnetite to reproduce titanium-poor titanomagnetites (Buddington and Lindsley, 1964;0'Reilly and Banerjee, 1967;Ozima and Larson, 1970;Kinoshita and Aoki, 1972;Nishitani and Kono, 1983).…”
Section: Thermal Analyses and Curie Temperatures (R C )mentioning
confidence: 99%